If it's not what You are looking for type in the equation solver your own equation and let us solve it.
.6(9x-6)=4x-3(2x-8)
We move all terms to the left:
.6(9x-6)-(4x-3(2x-8))=0
We multiply parentheses
5.4x-(4x-3(2x-8))-3.6=0
We calculate terms in parentheses: -(4x-3(2x-8)), so:We get rid of parentheses
4x-3(2x-8)
We multiply parentheses
4x-6x+24
We add all the numbers together, and all the variables
-2x+24
Back to the equation:
-(-2x+24)
5.4x+2x-24-3.6=0
We add all the numbers together, and all the variables
7.4x-27.6=0
We move all terms containing x to the left, all other terms to the right
7.4x=27.6
x=27.6/7.4
x=3+3.85714285714/5.28571428571
| .6(9x-6)=4x-3(2x-8 | | F(x)=9x^2+2 | | -2+d=1 | | 13u+4u-17u+4u-3u=4 | | 5(x-3)=2(4x+10) | | 7x+21=98 | | 6n+4-10=0 | | 5(x-3)=2(4x+0 | | 1/3y3−1/5y=5 | | 3(2x+5)=-3(x-4) | | 13u+4u–17u+4u–3u=4 | | 1/3y+3−1/5y=5. | | 5(x+-3)+(9)=46 | | 3(2x+2x+5)=-3(x-4) | | 5(x-3)-(-9)=46 | | (4x+15)=7x | | 3x+4x-2=7(x+2) | | 5y+12-2y=-7y-78 | | 4+3x=-29 | | (6-7i)/(-2-8i)=0 | | 12x^2-9=33x | | 5y+12-2y=-7-78 | | f(4)=5(4)-2 | | 3/2x-13=5x+1 | | (x+3)^2-1=35 | | -12k–-3k–14k+20k=-6 | | 10(4)^2x-1-5=7 | | 2(96+2w)=80-3w | | 8p–6p=12 | | (x+3)^2−1=35 | | x+1,5=6 | | 43h+2=17+5 |